Clinical profile in relation to age and gender of patients with temporomandibular disorders: a retrospective study - Han Qin; Shaoxiong Guo; Xiaohua Chen; Yifan Liu; Lei Lu; Mian Zhang; Hongyun Zhang; Jing Zhang; Shibin Yu (BMC, 2024)
Abstract Background The present study is to evaluate the clinical characteristics of patients with temporomandibular disorders (TMD). Methods A total of 3362 TMD patients were included. Each participant had complete medical records according to the diagnostic criteria for temporomandibular disorders (DC/TMD). The clinical characteristics including symptoms and signs in relation to age and gender were analyzed. Results The mean age of the patients seeking care was 29.89 ± 13.73Y, and 68.6% of patients were aged 16-35 years. The female-to-male ratio of patients was 2.2: 1, and the average age of males was significantly lower than that of females. The prevalence of clicking symptoms decreased with age, while the prevalence of pain symptoms and limitations in jaw movement increased with age. Females were more likely to have limitations in jaw movement than males. Among the patients with pain, the average visual analogue scale (VAS) was 2.96 ± 1.23. The average VAS score of acute TMD patients (≤ 3 months) was significantly higher than that of chronic TMD patients (> 3 months). Conclusions The majority of TMD patients seeking care were young people. The number and average age of female patients was higher than the males. Female patients were more likely to have limitations in jaw movement than males.